2022
DOI: 10.3390/ijms23031823
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-Functionalized Adsorbents Eliminate Central Effectors of Immunothrombosis, including Platelet Factor 4, High-Mobility Group Box 1 Protein and Histones

Abstract: Inflammation and thrombosis are closely intertwined in numerous disorders, including ischemic events and sepsis, as well as coronavirus disease 2019 (COVID-19). Thrombotic complications are markers of disease severity in both sepsis and COVID-19 and are associated with multiorgan failure and increased mortality. Immunothrombosis is driven by the complement/tissue factor/neutrophil axis, as well as by activated platelets, which can trigger the release of neutrophil extracellular traps (NETs) and release further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…Seraph-100) can remove these substances effectively. Ebeyer-Masotta et al [ 68 ] demonstrated that heparin-functionalised adsorbents efficiently depleted activated platelets, platelet-derived extracellular vesicles, PF4, HMGB1, and histones/nucleosomes. Similarly, Hogwood et al [ 69 ] demonstrated that heparin attenuates histones and NETs-induced inflammatory responses in whole blood.…”
Section: Pathogenesis Of Sepsismentioning
confidence: 99%
“…Seraph-100) can remove these substances effectively. Ebeyer-Masotta et al [ 68 ] demonstrated that heparin-functionalised adsorbents efficiently depleted activated platelets, platelet-derived extracellular vesicles, PF4, HMGB1, and histones/nucleosomes. Similarly, Hogwood et al [ 69 ] demonstrated that heparin attenuates histones and NETs-induced inflammatory responses in whole blood.…”
Section: Pathogenesis Of Sepsismentioning
confidence: 99%
“…None of the currently available anti-histone or anti-HMGB1 agents have been approved for immunomodulation in the management of critical illnesses by any clinical guideline due to the lack of evidence. Most recently, EBP using multiple hemofilters, such as Cytosorb [ 33 ], AN69ST membrane [ 34 ] and heparin-functionalized Seraph-100 blood filter [ 35 ], was found to adsorb circulating HMGB1 and histones in vitro and in vivo. It is noteworthy that the use of such EBP devices in patients with critical illness has great potential to mitigate HMGB1/histone-mediated inflammation, immune thrombosis and organ injury without the administration of traditional anti-histone or anti-HMGB1 agents.…”
Section: Introductionmentioning
confidence: 99%
“…While this extracorporeal approach is currently mainly explored regarding pathogen depletion, we have provided evidence that heparin-immobilized adsorbents may exert beneficial effects by binding and depleting mediators of immunothrombosis, including activated platelets and PF4 + pEVs, as well as HMGB1 and histones/nucleosomes ( Ebeyer-Masotta et al, 2022 ), as suggested in Figure 2 , and we are currently assessing the ability of heparin-functionalized adsorbents to deplete NETs.…”
Section: Therapeutic Potential Of Platelet-derived Ev Depletion Durin...mentioning
confidence: 99%